PENGARUH CITRA MERK, INOVASI , DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN GOJEK GO-RIDEâ€ (Studi Kasus Pada Masyarakat RT 015 Palmeriam) - Irfan Arif Husen; Desy Amaliati Setiawan (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this research is to determine the influence of brand image, Innovation, and price to customer satisfaction the community GOJEK GO-RIDE of RT 015 Palmeriam. Researcher used associative strategy.The sampling in this research used purposive sampling technique. The population in this study is the entire community of RT 015 Palmeriam customers and the data sample are 97 respondens. This research uses a corelation coefficient & determination coefficient, and hipotesis testing by IDM SPSS Statistics 25.0. Based on the results corelation coefficient, the result shows corelation coefficient partial brand image to customer satisfaction, about 0,163 with coefficient determination partial (KDP) 2,65%. Corelation coefficient partial innovation to customer satisfaction, about 0,235 with (KDP) 5,52%. Corelation coefficient partial price to customer satisfcation, about 0,474 with (KDP) 22,46%. Corelation coefficient simultaneus brand image, innovation, and price to customer satisfaction, about 0,784 with coefficient of multiple determination (KDB) 61,46%. Based on the result partial hipotesis testing, brand image has not significant effect to customer satisfaction with significant t 0,115 < 0,05. Innovation has a significant effect to customer satisfaction with significant t 0,022 < 0,05. Price has a significant effect to customer satisfaction with with significant t 0,000 < 0,05. Based on the results simultaneus hipotesis testing, brand image, innovation, and price has a significant effect to customer satisfaction with significant F 0,000 < 0,05